The Surgical Learning and Instructional Portfolio: What Residents at a Single Institution Are Learning - Webb, Travis P (The Accreditation Council for Graduate Medical Education, 2011)
BACKGROUND: The Accreditation Council for Graduate Medical Education (ACGME) Learning Portfolio is recommended as a tool to develop and document reflective, practice-based learning and improvement. There is no consensus regarding the appropriate content of a learning portfolio in medical education. Studying lessons selected for inclusion in their learning portfolios by surgical trainees could help identify useful subject matter for this purpose. METHODS: Each month, all residents in our surgery residency program submit entries into their individual Surgical Learning and Instructional Portfolio (SLIP). The SLIP entries from July 2008 to 2009 (n = 420) were deidentified and randomized using a random number generator. We conducted a thematic content analysis of 50 random portfolio entries to identify lessons learned. Two independent raters analyzed the “3 lessons learned” portion of the portfolio entries and identified themes and subthemes using the constant comparative method used in grounded theory. RESULTS: The collaborative coding process resulted in theme saturation after the identification of 7 themes and their subthemes. Themes in decreasing order of frequency included complications, disease epidemiology, disease presentation, surgical management of disease, medical management of disease, operative techniques, and pathophysiology. Junior residents chose to focus on a broad array of foundational topics including disease presentation, epidemiology, and overall management of diseases, whereas postgraduate year-4 (PGY-4) and PGY-5 residents most frequently chose to focus on complications as learning points. CONCLUSIONS: Lessons learned reflect perceived needs of the trainees based on training year. When given a template to follow, junior and senior residents choose to reflect on different subject matter to meet their learning goals.